A marvelous work and a wonder - Richards, Legrand (Salt Lake Sity (Utah) : Deseret Book Company, 1976)
Few books explain so clearly and concisely the fundamentals of the restored gospel of Jesus Christ as does A Marvelous work and a wonder. Those who master the basic principles in this best-selling volume will gain conviction, confidence, and understanding of the "marvelous work and a wonder" spoken of by Isaiah (29:14), which has come forth in our day.
The Church in this dispensation -- The Visit of the father and the son -- Personality of the father and the son --False doctrines and universal apostasy -- A marvelous work and a wonder to come forth -- The coming forth of the book of Mormon -- The book of Mormon fulfills bible prophecies -- Evidence of the divine authenticity of the book of Mormon -- Restoration of priesthood authority -- The ordinance of baptism -- The mission of the Holy Ghost -- Setting up the kingdom of God upon the Earth -- The Mission of Elijah -- Marriage for time and for all eternity -- The Gathering of Israel -- Israel in the latter days -- The Coming of Elias -- The True church, a missionary church -- Fundamental differences between salvation and exaltation -- Whence cometh man? -- Why is man here? -- Where is man going -- The Sabbath day -- Predestination and foreordination -- The Word of wisdom -- The Law of tithing -- By their fruits ye shall know them -- By their fruits ye shall know them (continued) -- Summary
Includes index.
Keywords: BOOK OF MORMON -- EVIDENCE, AUTHORITY, ETC